Increased Heart Rate Is Associated With Higher Mortality in Patients With Atrial Fibrillation (AF): Results From the Outcomes Registry for Better Informed Treatment of AF (ORBIT‐AF). Issue 9 (14th September 2015) - Steinberg, Benjamin A.; Kim, Sunghee; Thomas, Laine; Fonarow, Gregg C.; Gersh, Bernard J.; Holmqvist, Fredrik; Hylek, Elaine; Kowey, Peter R.; Mahaffey, Kenneth W.; Naccarelli, Gerald; Reiffel, James A.; Chang, Paul; et al.
Abstract : Background: Most patients with atrial fibrillation (AF) require rate control; however, the optimal target heart rate remains under debate. We aimed to assess rate control and subsequent outcomes among patients with permanent AF. Methods and Results: We studied 2812 US outpatients with permanent AF in the Outcomes Registry for Better Informed Treatment of Atrial Fibrillation. Resting heart rate was measured longitudinally and used as a time‐dependent covariate in multivariable Cox models of all‐cause and cause‐specific mortality during a median follow‐up of 24 months. At baseline, 7.4% (n=207) had resting heart rate <60 beats per minute (bpm), 62% (n=1755) 60 to 79 bpm, 29% (n=817) 80 to 109 bpm, and 1.2% (n=33) ≥110 bpm. Groups did not differ by age, previous cerebrovascular disease, heart failure status, CHA2 DS2 ‐VASc scores, renal function, or left ventricular function. There were significant differences in race ( P =0.001), sinus node dysfunction ( P =0.004), and treatment with calcium‐channel blockers ( P =0.006) and anticoagulation ( P =0.009). In analyses of continuous heart rates, lower heart rate ≤65 bpm was associated with higher all‐cause mortality (adjusted hazard ratio [HR], 1.15 per 5‐bpm decrease; 95% CI, 1.01 to 1.32; P =0.04). Similarly, increasing heart rate >65 bpm was associated with higher all‐cause mortality (adjusted HR, 1.10 per 5‐bpm increase; 95% CI, 1.05 to 1.15; P <0.0001). This relationship was consistent across endpoints and in a broader sensitivity analysis of permanent and nonpermanent AF patients. Conclusions: Among patients with permanent AF, there is a J‐shaped relationship between heart rate and mortality. These data support current guideline recommendations, and clinical trials are warranted to determine optimal rate control. Clinical Trial Registration: URL:http://clinicaltrials.gov/ . Unique identifier: NCT01165710.